Studi Limbah Bahan Berbahaya dan Beracun (B3) Oli Bekas dan Sampah Terkontaminasi Oli Bekas pada Bengkel Motor di Kota Banjarbaru - Widyanor, Julian; Firmansyah, Muhammad; Mahyudin, Rizqi Puteri; Prihatini, Nopi Stiyati; Firdausy, Muhammad Abrar (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
The number of uses of transportation equipment such as motorcycles continues to increase every day along with the number of populations that increases every year. Motorcycles are most often used by the community because motorcycles are quite affordable and more flexible for people with a high enough level of mobility. The increasing demand for motorcycles must be offset by the addition of services for these motorcycles such as workshops, where workshop activities produce waste in the form of hazardous and toxic materials (B3) waste such as used oil, used oil filters, used oil packaging bottles and also cloth contaminated by used oil. The purpose of the study is to identify the amount of B3 waste generation, management of packaging, storage/collection, and licensing and transportation of B3 waste. The calculation of B3 waste generation is carried out by taking sample data and questionnaires at each Type-B motorcycle workshop which amounts to 12 workshops and is carried out for 12 days. The average B3 waste generation per workshop at each Type-B motorcycle workshop in Banjarbaru City is for used oil accommodated as much as 8.24 liters/workshop/day, used oil filters as much as 0.40 pieces/workshops/day, waste washcloths/used fields as much as 2.53 sheets/workshops/day and used oil packaging as much as 15.33 bottles/workshops/day. B3 waste management at two-wheeled motorcycle workshops in Banjarbaru City has still not been by applicable regulations.